The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.3892/ijmm.2014.1674
|View full text |Cite
|
Sign up to set email alerts
|

Somatic GATA5 mutations in sporadic tetralogy of Fallot

Abstract: Abstract. Tetralogy of Fallot (TOF) is the most common form of cyanotic congenital heart disease, with high morbidity and mortality rates. Accumulating evidence has demonstrated that genetic defects play an important role in the pathogenesis of TOF. However, the molecular basis of TOF in the majority of patients remains to be determined. In the present study, sequence analysis of the coding exons and exon-intron boundaries of GATA5, a gene encoding a zinc finger-containing transcriptional factor crucial for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…In humans, a great number of GATA5 mutations have been previously associated with various congenital cardiovascular deformities, including atrial septal defect, ventricular septal defect, tetralogy of Fallot, double outlet right ventricle, aortic stenosis, patent ductus arteriosus and bicuspid aortic valve (40)(41)(42)(43)(44). In the present study, all the mutation carriers had DCM, but only 2 mutation carriers also had ventricular septal defect.…”
Section: Discussionsupporting
confidence: 49%
“…In humans, a great number of GATA5 mutations have been previously associated with various congenital cardiovascular deformities, including atrial septal defect, ventricular septal defect, tetralogy of Fallot, double outlet right ventricle, aortic stenosis, patent ductus arteriosus and bicuspid aortic valve (40)(41)(42)(43)(44). In the present study, all the mutation carriers had DCM, but only 2 mutation carriers also had ventricular septal defect.…”
Section: Discussionsupporting
confidence: 49%
“…The human cardiac full-length cDNA was prepared as previously described (22,23,(36)(37)(38). Human HAND2 harboring the whole coding region was generated by PCR with the human heart cDNA as a template, cut with the restriction enzymes, EcoRI and NotI, and then subcloned at the EcoRI-NotI sites of the pcDNA3.1 vector (Invitrogen, Carlsbad, CA, USA).…”
Section: Expression Plasmids and Site-directed Mutagenesismentioning
confidence: 99%
“…Cardiogenesis from the early embryo to the formation of a fully functional four-chambered heart is a complex and dynamic process that necessitates a harmonious concerto of transcription factors, adhesion molecules, ion channels, signaling molecules and structural proteins, and both environmental and genetic risk factors may disrupt this biological process of heart development, resulting in a wide variety of CHDs (12). Although environmental exposures are also relevant, a growing number of studies have demonstrated that genetic defects are the leading cause of CHD, and thus far, mutations in >60 genes have been causally linked to CHD (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Among these CHD-causative genes, those encoding cardiac transcription factors, including homeodomain-containing protein, NK2 homeobox 5 (NKX2.5), GATA-binding protein 4 (GATA4) and T-box transcription factor 5 (TBX5), are the most commonly involved genes in the pathogenesis of CHD, underscoring the pivotal roles of cardiac transcription factors in cardiovascular development and disease (26).…”
Section: Introductionmentioning
confidence: 99%
“…As a part of a conserved regulatory network, these core cardiac transcription factors physically interact with each other to finely regulate cardiac development and structural remodeling [6][7][8]. Therefore, it is not surprising that an increasing number of mutations in these core cardiac transcription factors, especially for the most extensively investigated NKX2-5, GATA4, GATA5, GATA6, TBX5, and TBX20, have been identified in patients with various CHDs or cardiac arrhythmias [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. More interestingly, mutations in some cardiac transcription factors, such as NKX2-5, GATA4, GATA5, GATA6 and TBX5, have also been associated with isolated DCM in humans [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%